Pengembangan Media Ular Tangga Pintar Pada Pembelajaran IPA Kelas IV SDN 07 Koto Panai Air Haji - Silvina Andrianto; Firman Firman; Desyandri Desyandri (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to produce valid and practical learning media for smart and ladder snakes in class IV science subjects. This type of research uses research and development. Learning media was developed using the ADDI model. This research was conducted in the odd semester of the 2020/2021 school year. Collecting data regarding the validity of smart learning media for science subjects in grade IV SD was developed and used a questionnaire validated by experts. For practicality, smart learning media, the circle of stairs is carried out in schools by teachers and students. The results of the validation of the smart learning media in the fourth grade science subject of SD are in the very valid category of 94.1% and the validation of the material on the smart ladder snake learning media is in the very valid category with 91%. The smart ladder game media that has been developed are categorized as very practical by educators by 96% and categorized as very practical by students by 97%. The learning media for snakes and ladders in science subjects for grade IV SD that are produced are very valid and very practical to be used in science subjects in grade IV SD. Researcher's suggestion is that the learning media for snakes and ladders in science subjects in grade IV SD that have been developed can be used as media in the learning process in the classroom. Keywords: Development, Science Learning Media, Smart Ladder Snake